(untitled) (Research, Society and Development, 2022)
The objective of this work is to evaluate whether the overseeding of annual forage grasses in soybean contributes to the reduction of weed density for the subsequent crop, as well as provides forage to meet the demand for animal feed so that its ground cover does not interfere with subsequent winter crop yield. Two cultivars of dual-purpose wheat (BRS Tarumã and BRS Pastoreio), three of rye (BRS Serrano, BRS Progresso and Temprano) and of black oat (Embrapa 139 Neblina, BRS Madrugada and BRS Centauro), one of millet (BRS 1503) and one of Sudan grass (BRS Estribo). The experiments were carried out in two municipalities in Rio Grande do Sul, Brazil, in 2019 and 2020. The forages were manually oversown at the R6 stage of soybean, in a randomized block design, in three replications, for two years. . Initial forage stand, subsequent crop yield, weed density before forage sowing, after forage desiccation for wheat sowing and during wheat tillering, dry mass (DM) production of forages in the vegetative phase, the total DM production during the forage cycle before desiccation for wheat sowing. The initial forage stand was compromised by the lack of rain, mainly in 2020, causing damage to DM production and the persistence of straw. The treatments did not affect wheat productivity and weed density.